IRSIYATNING MOLEKULYAR ASOSLARI. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article examines the molecular foundations of heredity based on the achievements of modern molecular biology and genetics. The structure and functional roles of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) as the main carriers of genetic information are analyzed. The molecular mechanisms of genetic information expression, including replication, transcription, and translation processes, are described in detail. Special attention is given to the concept of genes, the genetic code, and mutations, as well as their significance in the formation of hereditary traits and genetic disorders. The practical importance of studying the molecular basis of heredity for medicine, biotechnology, and biological sciences is substantiated.